2002
DOI: 10.1097/00004770-200205000-00010
|View full text |Cite
|
Sign up to set email alerts
|

The Sealing Ability and Retention Characteristics of Mineral Trioxide Aggregate in a Model of Apexification

Abstract: Treatment of the immature pulpless tooth presents both an endodontic and restorative challenge. A more favorable long-term prognosis may be achieved with a mineral trioxide aggregate (MTA) apexification procedure followed by an internal bonding technique. We investigated the efficacy of this treatment option by testing the sealing ability and retention characteristics of MTA when placed as an apical barrier in a standardized in vitro open apex model. MTA was placed as an apical barrier at a thickness of 1 mm o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
234
2
13

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(257 citation statements)
references
References 16 publications
8
234
2
13
Order By: Relevance
“…The sealing ability and retention characteristics of MTA in a model of apexification was tested in an in vitro study using human, extracted, single-rooted teeth. 38 Some leakage was recorded in this study, but this was thought to be as a result of the intracanal delivery technique rather than the material itself.…”
Section: Apexificationmentioning
confidence: 72%
See 1 more Smart Citation
“…The sealing ability and retention characteristics of MTA in a model of apexification was tested in an in vitro study using human, extracted, single-rooted teeth. 38 Some leakage was recorded in this study, but this was thought to be as a result of the intracanal delivery technique rather than the material itself.…”
Section: Apexificationmentioning
confidence: 72%
“…7). 38 This should then be evaluated radiographically and if the MTA appears poorly condensed it can be rinsed out with sterile water and the procedure repeated. Any traces of excess MTA on the post preparation wall can be removed with a moist paper point.…”
Section: Clinical Procedures Placement Of Apical Mta Plugmentioning
confidence: 99%
“…Some research has shown that the remains of calcium hydroxide on the dentinal walls had no significant effect on MTA microleakage 8 . In contrast, others have suggested that the remnants react and form calcium carbonate, which interferes with apical sealing 19 .Others have suggested that the combination of calcium hydroxide and MTA in apexification procedures may favorably influence the regeneration of the periodontium 9 .…”
Section: Discussionmentioning
confidence: 97%
“…18 Glass fiber posts are an alternative for the restoration of teeth with IR due they have modulus of elasticity similar to dentine. 19,20 The use of an apical plug with MTA has been suggested for endodontic therapy of teeth with IR, [21][22][23] resulting in a faster treatment and inducing the mineralized tissue formation in the root apex. 24 The root canal filling using Epiphany/…”
Section: 10mentioning
confidence: 99%